IgG4-related disease with nasopharyngeal malignancy-like manifestations - Lin, Xijun; Lin, Peiliang; Fan, Jianming; Zhang, Biying; Liang, Faya; Han, Ping; Liu, Xiang; Huang, Xiaoming (Frontiers in Immunology, 2024)
BACKGROUND: IgG4-related disease (IgG4-RD) was characterized by single or multiple masses in organs, which may mimic various inflammatory and malignant diseases. Here, we summarize 4 patients with aggressive manifestations of IgG4-RD that mimic nasopharynx cancer to provide some new sights for the diagnosis of IgG4-RD. CASE SUMMARY: Four patients were included in our series. The age ranged from 53 to 64 years old, and the duration of the disease ranged from 4 to 6 months. The chief complaints included headache, rhinorrhea, or diplopia. All patients had more than 10 IgG4+ plasma cells/HPF in immunohistochemistry with plasma lgG4 levels ranging from 218 mg/dL to 765 mg/dL. All of them met the diagnostic criteria of lgG4-RD. CONCLUSION: The described case is highly similar to the clinical manifestations of nasopharyngeal carcinoma. Although pathology is the gold standard, there are still limitations. Serological IgG4 can help confirm the diagnosis. Timely diagnosis of IgG4-RD is of great significance in preventing secondary organ damage in patients with active diseases.